PERSEPSI AUDITOR TENTANG PENGARUH ETIKA, KOMPETENSI, DAN INDEPENDENSI TERHADAP KUALITAS AUDIT DENGAN UNDANG-UNDANG NO. 5 TAHUN 2011 TENTANG AKUNTAN PUBLIK SEBAGAI VARIABEL MODERASI - Eni Suparni, Dewi Saptantinah Puji Astuti & Fadjar Harimurti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2017)
Public Accounting Firm in their profession trying to improve audit quality isgood, that produce audit reports to present the findings and report the truth aboutthe financial condition of its clients, including when it occurs in violation of theclient's accounting system. The purpose of this study were: 1) to analyze thesignificance of the influence of ethics, competence of auditors, auditor independence,and Law No. 5 of 2011 on Public Accountant to audit quality in the publicaccounting firm of Surakarta and Yogyakarta. 2) to analyze the moderating effects ofLaw No. 5 of 2011 on Public Accountant ethics influence the competence of auditorsand auditor independence on audit quality in the public accounting firm of Surakartaand Yogyakarta. This study uses survey method, the type of data used quantitativeand qualitative data, the data source used primary data and secondary data. Thepopulation in this study are all auditors who work in public accounting firms in theregion of Surakarta and Yogyakarta. The number of samples in the study based onthe number of questionnaires returned, as many as 53 respondents. The samplingtechnique using random sampling. Data collection methods are used: questionnairesand documentation. Data analysis technique used to test the validity, reliability test,classic assumption test and multiple linear regression analysis and test of absolutedifference. In conclusion that ethics, the competence of auditors, auditorindependence, and Law No. 5 of 2011 on Public Accountant positive and significantimpact on audit quality in the public accounting firm of Surakarta and Yogyakarta.Law No. 5 of 2011 on Public Accountant does not moderate the effect of variableethics, competence of auditors, auditor independence on audit quality.Keywords: ethics, competence, independence, Act No. 5 of 2011, audit quality.